Discovery of the principal specific transcription factors of Apicomplexa and their implication for the evolution of the AP2-integrase DNA binding domains - Balaji, S. (Oxford University Press, 2005)
The comparative genomics of apicomplexans, such as the malarial parasite Plasmodium, the cattle parasite Theileria and the emerging human parasite Cryptosporidium, have suggested an unexpected paucity of specific transcription factors (TFs) with DNA binding domains that are closely related to those found in the major families of TFs from other eukaryotes. This apparent lack of specific TFs is paradoxical, given that the apicomplexans show a complex developmental cycle in one or more hosts and a reproducible pattern of differential gene expression in course of this cycle. Using sensitive sequence profile searches, we show that the apicomplexans possess a lineage-specific expansion of a novel family of proteins with a version of the AP2 (Apetala2)-integrase DNA binding domain, which is present in numerous plant TFs. About 20–27 members of this apicomplexan AP2 (ApiAP2) family are encoded in different apicomplexan genomes, with each protein containing one to four copies of the AP2 DNA binding domain. Using gene expression data from Plasmodium falciparum, we show that guilds of ApiAP2 genes are expressed in different stages of intraerythrocytic development. By analogy to the plant AP2 proteins and based on the expression patterns, we predict that the ApiAP2 proteins are likely to function as previously unknown specific TFs in the apicomplexans and regulate the progression of their developmental cycle. In addition to the ApiAP2 family, we also identified two other novel families of AP2 DNA binding domains in bacteria and transposons. Using structure similarity searches, we also identified divergent versions of the AP2-integrase DNA binding domain fold in the DNA binding region of the PI-SceI homing endonuclease and the C-terminal domain of the pleckstrin homology (PH) domain-like modules of eukaryotes. Integrating these findings, we present a reconstruction of the evolutionary scenario of the AP2-integrase DNA binding domain fold, which suggests that it underwent multiple independent combinations with different types of mobile endonucleases or recombinases. It appears that the eukaryotic versions have emerged from versions of the domain associated with mobile elements, followed by independent lineage-specific expansions, which accompanied their recruitment to transcription regulation functions.